Influence of wine phenolic compounds on viability and exopolysaccharide production by Pediococcus pentosaceus - Stivala, Maria Gilda (2018)
Low molecular weight phenolic fractions of Cabernet Sauvignon (LMF-C) and Malbec (LMF-M) wines from Colalao del Valle, Tucuman, Argentina, were isolated and chemically characterized. The effect of these phenolic fractions on viability and exopolysaccharide production of Pediococcus pentosaceus E2p, a wine spoilage bacterium, was examined in synthetic wine-like medium (SWM). The concentration of phenolic acids detected in LMF-C was 47.28% higher than that determined in LMF-M. The presence of LMF-C and LMF-M at concentration four times higher than detected in wine, produce a decrease in viable cells from the inoculum of 3.01 and 3.65 Log cfu mL-1, respectively and sometimes a significantly decrease in exopolysaccharide release was detected for both fractions. Considering the current trend in the search of potential and effective antimicrobial agents for total or partial replacement of sulfites in the winemaking process, these results could be of great interest, even thought that phenolic compounds can also add extra value to the final product, considering their recognized beneficial properties on human health.